2020
DOI: 10.1002/jcla.23081
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose atorvastatin improves vascular endothelial function in patients with leukoaraiosis

Abstract: Objective Leukoaraiosis (LA), as an age‐related white matter degeneration, is mainly caused by chronic ischemia. Our study aims to explore the efficacy of different doses of atorvastatin (ATV) in the vascular endothelial function in patients with LA. Methods Our study enrolled 402 LA patients who were then randomly included as control or treated with ATV (10 mg), ATV (20 mg), or ATV (30 mg). The total cholesterol (TC), triglycerides (TG), high‐density lipoprotein cholesterol (HDL‐C), and low‐density lipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…17 Leukoaraiosis is expected in the elderly and is associated with recurrent stroke, cognitive decline, gait disturbances, hemorrhagic transformation, and functional abnormalities after ischemic stroke. 18,19 Most studies have investigated the correlation between active stroke and leukoaraiosis severity using computed tomography visual scales or volumetric measurements.…”
Section: Discussionmentioning
confidence: 99%
“…17 Leukoaraiosis is expected in the elderly and is associated with recurrent stroke, cognitive decline, gait disturbances, hemorrhagic transformation, and functional abnormalities after ischemic stroke. 18,19 Most studies have investigated the correlation between active stroke and leukoaraiosis severity using computed tomography visual scales or volumetric measurements.…”
Section: Discussionmentioning
confidence: 99%
“…352 The precise mechanism that mediates the effectiveness of statins therapy for retarding LA progression remains unclear to date. Statins may help to delay the progression of LA through pleiotropic mechanisms including improving endothelial function and cerebral vasoreactivity, [354][355][356] attenuating inflammatory response, 357,358 and decreasing oxidative stress. 358,359 Although more evidence described above seem to suggest statins as an efficient treatment against LA, the lipid-lowering treatment may have to be cautiously managed due to some conflicting findings that statin treatment was associated with increased risk of LA worsening.…”
Section: Lipid Controlmentioning
confidence: 99%
“…The precise mechanism that mediates the effectiveness of statins therapy for retarding LA progression remains unclear to date. Statins may help to delay the progression of LA through pleiotropic mechanisms including improving endothelial function and cerebral vasoreactivity [ 354 - 356 ], attenuating inflammatory response [ 357 , 358 ], and decreasing oxidative stress [ 358 , 359 ].…”
Section: Management Of Lamentioning
confidence: 99%
“…Xue et al enrolled 402 LA patients who were then randomly included as control or treated with atorvastatin (ATV) (10 mg), ATV (20 mg) or ATV (30 mg). Their research showed that high-dose atorvastatin can improve vascular endothelial function in patients with LA (Xue et al, 2020). In addition to undertaking the abovementioned treatment, doctors should also actively treat the basic underlying diseases such as hypertension and diabetes.…”
Section: Differential Diagnosis Of Leukoaraiosismentioning
confidence: 99%